2017
DOI: 10.3892/mmr.2017.6587
|View full text |Cite
|
Sign up to set email alerts
|

RPN11 deubiquitinase promotes proliferation and migration of breast cancer cells

Abstract: The deubiquitinase enzyme RPN11 is involved in oncogenesis in various types of cancer. However, in breast cancer, the expression levels, prognostic relevance and biological function of RPN11 remains unclear. In the present study, RPN11 expression levels in breast cancer tissues and adjacent non‑tumor tissues were determined by reverse transcription‑quantitative polymerase chain reaction and immunohistochemical staining, and the association of RPN11 with clinicopathological features of breast cancer was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 27 publications
3
50
0
Order By: Relevance
“…We analyzed the correlation between seven prognostic genes (PSMD14, RBM45, PSMD1, OLA1, including HCC, esophageal cancer, breast cancer [5,[12][13]. Our results are in accordance with these studies, implying that PSMD14 could be a potential prognostic gene for HCC [5].…”
Section: Seven Genes Expression Is Correlated With Immune Infiltratiosupporting
confidence: 82%
See 1 more Smart Citation
“…We analyzed the correlation between seven prognostic genes (PSMD14, RBM45, PSMD1, OLA1, including HCC, esophageal cancer, breast cancer [5,[12][13]. Our results are in accordance with these studies, implying that PSMD14 could be a potential prognostic gene for HCC [5].…”
Section: Seven Genes Expression Is Correlated With Immune Infiltratiosupporting
confidence: 82%
“…PSMD14 has been confirmed to play vital roles in gene ontology and related pathway, including protein stability [6], tumour formation [7], transcriptional regulation [8], double-strand DNA break repair [9], senescence [10], apoptosis and resistance [11], growth and metastasis [5], BMP6 signaling [6], TGF-β signaling [8]. Recently, PSMD14 has been overexpressed in many human cancers, such as HCC, colorectal cancer, multiple myeloma, esophageal squamous cell carcinoma and breast cancer, which it This is related to the poor prognosis of the patients [5,6,[11][12][13]. PSMD14 acts as an oncogene that promotes tumor progression by deubiquitinating of different protein substrates.…”
Section: Introductionmentioning
confidence: 99%
“…PSMD14 is a deubiquitinating enzyme responsible for substrate deubiquitination during proteasomal degradation. Although the role of PSMD14 has been reported in several cancer types [17,19,21,22,25,34], its involvement in lung cancer has not been elucidated. In this study, we found that the level of PSMD14 was significantly upregulated in NSCLC tissues, suggesting its tumor-promoting effects in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…PSMD14 is involved in a series of important physiological and pathological processes such as DNA damage repair [13][14][15][16], tumor formation [17][18][19], and inflammation [20]. PSMD14 promotes cell growth and proliferation of gliomas, colon cancer, liver cancer, esophageal cancer, and breast cancer, and enhances the resistance of tumor cells to radiation and Ivyspring International Publisher chemotherapy drugs [17][18][19][20][21][22][23]. Reduced PSMD14 expression inhibits tumor growth by inducing cell cycle arrest, senescence, or apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation